Application of SWOT analysis, goal setting, and mission statements in training to improve students' career maturity - Fian Rizkyan Surya Pambuka; Moh Wahyu Madina; June Maulana Ikhsan; Emamiridya Erine Yupi; Eny Purwandari (Community Empowerment, 2024)
Career maturity is a crucial aspect for senior high school students as they begin to consider their future academic paths and career planning. However, many students face difficulties in this process. This community service activity aimed to enhance students' career maturity. The method employed was service learning, incorporating SWOT analysis, goal setting, and reflective mission statements through a combination of lectures, discussions, and Q&A sessions. The results indicate a significant improvement in students' career maturity, as evidenced by two main indicators. Firstly, the career decision-making score increased significantly from 137.83 (pre-test) to 151.43 (post-test). Secondly, student feedback revealed that they felt more confident in their choice of major and career planning, and had a broader perspective on various academic programs and careers.